Sporadic gastric carcinoid tumor successfully treated by two-stage laparoscopic surgery: A case report - Kinoshita, Takahiro (Baishideng Publishing Group Co., Limited, 2010)
We report a case of sporadic gastric carcinoid tumor successfully treated by two-stage laparoscopic surgery. A 38-year old asymptomatic woman was referred to our hospital for evaluation of a submucosal tumor of the stomach. Endoscopic examination showed a solitary submucosal tumor without ulceration or central depression on the posterior wall of the antrum and biopsy specimens were not sufficient to determine the diagnosis. Endoscopic ultrasound revealed a tumor nearly 2 cm in diameter arising from the muscle layer and a computed tomography scan showed the tumor enhanced in the arterial phase. Laparoscopic wedge resection was performed for definitive diagnosis. Pathologically, the tumor was shown to be gastric carcinoid infiltrating the muscle layer which indicated the probability of lymph node metastasis. Serum gastrin levels were normal. As a radical treatment, laparoscopy-assisted distal gastrectomy with regional lymphadenectomy was performed 3 wk after the initial surgery. Finally, pathological examination revealed no lymph node metastasis.